Knowledge, Attitude, and Perception of Medical Students Towards a Career in Anesthesiology - Chidera Onwuka; Daniel David OTOBO; Maryann ONIPE; Isaac Firebrand INAMU; Stephanie Hotton ANTHONY (International Journal of Medical Students)
BACKGROUND Anesthesia is a crucial specialty in the medical field as it transcends both medical and surgical specializations. However, it is vital to Global Surgery. AIM: This study aims to assess and evaluate the knowledge, attitudes and perceptions of medical   students   towards anesthesiology and a career in it.